Association between changes in body fat and disease progression after breast cancer surgery is moderated by menopausal status - Li-Ni Liu; Yung-Chang Lin; Christine Miaskowski; Shin-Cheh Chen; Mei-Ling Chen (BMC Cancer, 2017)
Abstract Background Obesity is linked to poor disease outcomes in breast cancer patients. However, this link was mostly based on body weight or BMI rather than body-fat. The purpose of this study was to evaluate the relationship between body-fat gain and disease progression in Taiwanese women after breast cancer surgery and how this relationship is influenced by menopausal status. Methods Body fat percentage was measured 1 day before and 6 months after surgery in 131 women with stages 0–III breast cancer. Disease outcomes (metastasis and death) were assessed by chart review and telephone contact 7 to 8 years after diagnosis. These data were analyzed by multivariate Cox proportional hazard model analysis. Results The percentage of women with over 5% gain in body-fat was 56% for premenopausal and 42% for postmenopausal. Rates of distant metastasis and all-cause mortality were 17.6 and 9.9%, respectively over the follow-up period. Distant metastases were predicted in postmenopausal but not premenopausal women with breast cancer by increased body fat percentage (HR = 1.3, p = 0.035), after controlling other potential covariates, including disease severity, estrogen receptor expression, progesterone receptors expression, age, and exercise habit before diagnosis. Survival was not significantly associated with body-fat percentage gains. Conclusions Our results suggest that increased body fat percentage 6 months after breast surgery is an important predictor of distant metastasis in postmenopausal Taiwanese women with breast cancer. Clinicians may need to measure patients’ body fat periodically. Our findings should be validated in studies with a longer follow-up time.